Ambiguitas Norma dan Problem Teknikalitas Dispensasi Kawin pada Peradilan Agama di Indonesia (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2023)
This study aims to discuss the norms regarding the minimum marriage age and dispensation for marriage, which appear contradictory, although both are within the same law. This study employs a normative-empirical juridical approach with a judicial case study type. The normative data sources include Law Number 1 of 1974 and Law Number 16 of 2019, while the normative-empirical data consists of two judicial decisions from the Talu Religious Court. The study finds that dispensation for marriage should not be deemed a direct factor contributing to the high incidence of early marriages because this norm is not a direct instrument to curb early marriages. The relevant instruments to address early marriages are community awareness and empowerment. In certain aspects, the norm regarding marriage dispensation is also related to the status or legitimacy of children, especially when a woman applying for dispensation is already pregnant (out of wedlock). However, formally, the Compilation of Islamic Law has already clarified that legitimate children are those born within a valid marriage, without considering whether the pregnancy occurred within a valid marriage or not.